Loss of PTEN stabilizes the lipid modifying enzyme cytosolic phospholipase A(2)α via AKT in prostate cancer cells - Vignarajan, Soma (Impact Journals LLC, 2014)
Aberrant increase in pAKT, due to a gain-of-function mutation of PI3K or loss-of-function mutation or deletion of PTEN, occurs in prostate cancer and is associated with poor patient prognosis. Cytosolic phospholipase A(2)α (cPLA(2)α) is a lipid modifying enzyme by catalyzing the hydrolysis of membrane arachidonic acid. Arachidonic acid and its metabolites contribute to survival and proliferation of prostate cancer cells. We examined whether AKT plays a role in promoting cPLA(2)α action in prostate cancer cells. We found a concordant increase in pAKT and cPLA(2)α levels in prostate tissue of prostate epithelial-specific PTEN-knockout but not PTEN-wide type mice. Restoration of PTEN expression or inhibition of PI3K action decreased cPLA(2)α expression in PTEN-mutated or deleted prostate cancer cells. An increase in AKT by Myr-AKT elevated cPLA(2)α protein levels, which could be diminished by inhibition of AKT phosphorylation without noticeable change in total AKT levels. pAKT levels had no influence on cPLA(2)α at mRNA levels but reduced cPLA(2)α protein degradation. Anti-AKT antibody co-immunoprecipitated cPLA(2)α and vice versa. Hence, AKT plays a role in enhancing cPLA(2)α protein stability in PTEN-null prostate cancer cells, revealing a link between oncogenic pathway and lipid metabolism.